Isopyrazole‐Masked Tetraketone: Tautomerism and Functionalization for Fluorescent Metal Ligands. Issue 30 (16th August 2021) - Shirakura, Hayato; Manabe, Yumehiro; Kasai, Chika; Inaba, Yuya; Tsurui, Makoto; Kitagawa, Yuichi; Hasegawa, Yasuchika; Yoneda, Tomoki; Ide, Yuki; Inokuma, Yasuhide
Abstract: An isopyrazole (4 H ‐pyrazole)‐embedded nonane‐2, 4, 6, 8‐tetraone derivative was synthesized as a masked‐tetraketone for stepwise and multiple functionalization. The masked‐tetraketone has six possible tautomers, but exists predominantly as a 12π‐electron conjugated keto‐enamine‐imine‐enol form, which was also observed in the solid state by single crystal X‐ray analysis. Stepwise functionalization to introduce metal‐coordination and fluorescence‐enhancement sites into the masked tetraketone furnished a fluorescent chromophore that indicates metal coordination on a microgram scale by considerably changing the solid‐state emission. Abstract : Isopyrazole‐masking strategy allowed to control complicated tautomerism of a nonane‐2, 4, 6, 8‐tetraone derivative having a natural type polyketone sequence. Stepwise, multiple functionalization of isopyrazole‐masked tetraketone furnished a fluorescent metal ligand that considerably changes solid‐state emission upon metal coordination.